Bischof Eustathios im Paradies: Eine Kirche und ihr Stifter im kappadokischen Parnassos - Melih ARSLAN (Akdeniz University, 2021)
After years of illicit digging and demolition a church has been excavated in Parnassos of Cappadocia, situated at the border to Galatia, between Tuz Gölü and Halys. It is the first excavation in Parnassos, and a three-aisled basilica with formidable mosaics as well as a building inscription came to light, the latter giving us a glimpse of the church hierarchy in late antique Parnassos. Mosaics are very rare in Cappadocia. The impressive and highly decorated floor of the main room depicts several animals, trees and plants in paradise. It is a motif often used in Cilicia and Syria in the 5th century. A mosaic inscription is placed in the centre, naming three men who were connected to the construction of the church, including a bishop called Eustathios. Also a date is given as year 494 in the 15th indiction. There are several possible interpretations, but we suggest the church was built in 462 and Eustathios is to be identified with the already well known bishop who actively participated in the theological debates of his time.